Dichotomous splicing signals in exon flanks - Zhang, Xiang H-F.; Leslie, Christina S.; Chasin, Lawrence A. (Genome Research, 2005)
Intronic elements flanking the splice-site consensus sequences are thought to play a role in pre-mRNA splicing. However, the generality of this role, the catalog of effective sequences, and the mechanisms involved are still lacking. Using molecular genetic tests, we first showed that the ∼50-nt intronic flanking sequences of exons beyond the splice-site consensus are generally important for splicing. We then went on to characterize exon flank sequences on a genomic scale. The G+C content of flanks displayed a bimodal distribution reflecting an exaggeration of this base composition in flanks relative to the gene as a whole. We divided all exons into two classes according to their flank G+C content and used computational and statistical methods to define pentamers of high relative abundance and phylogenetic conservation in exon flanks. Upstream pentamers were often common to the two classes, whereas downstream pentamers were totally different. Upstream and downstream pentamers were often identical around low G+C exons, and in contrast, were often complementary around high G+C exons. In agreement with this complementarity, predicted base pairing was more frequent between the flanks of high G+C exons. Pseudo exons did not exhibit this behavior, but rather tended to form base pairs between flanks and exon bodies. We conclude that most exons require signals in their immediate flanks for efficient splicing. G+C content is a sequence feature correlated with many genetic and genomic attributes. We speculate that there may be different mechanisms for splice site recognition depending on G+C content.